Evaluation of the BD GeneOhm MRSA and VanR Assays as a Rapid Screening Tool for Detection of Methicillin-Resistant Staphylococcus aureus and Vancomycin-Resistant Enterococci in a Tertiary Hospital in Saudi Arabia - H. Hassan; M. Shorman (International Journal of Microbiology)
Objectives. The aim of this study was to evaluate the diagnostic performance of BD GeneOhm VanR Assay, a rapid PCR test that detects the presence of vanA and/or vanB genes and the performance of BDGeneOhm MRSA Assay which detects the staphylococcal cassette chromosomemec (SCCmec cassette) carrying the mecA gene and Staphylococcus aureus specific sequence located within the orfX gene. Methods. 300 duplicate rectal swabs collected consecutively were analyzed for the presence of VRE by culture and BD PCR. 2267 duplicate swabs were collected (728 nasal and 1539 groin swabs) and analyzed for the presence of MRSA by culture method and BD PCR. Results. Compared to culture, the BD GeneOhm VanR Assay showed a sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 100%, 91.1%, 23.5%, and 100%, respectively. The BD GeneOhm MRSA Assay revealed sensitivity, specificity, PPV, and NPV of 97.2%, 99.4%, 89.7%, and 99.9%, respectively, for nasal swabs. For groin swabs, it was 100%, 98.7%, 61.5% and 100%, respectively. Conclusion. The BD GeneOhm vanR Assay is a good screening test for rapid exclusion of VRE carriers in hospitals. The BD GeneOhm MRSA Assay represents a reliable screening test. The true strength of the BD GeneOhm Assay for MRSA and VRE is its exceptionally high NPV making the test an ideal tool for rapid exclusion of MRSA and VRE carriers in hospitals. As a consequence, this would dramatically shorten the patient isolation time.